An Efficient TDC Using a Dual-Mode Resource-Saving Method Evaluated in a 28-nm FPGA - Parsakordasiabi, Mojtaba; Vornicu, Ion; Rodriguez-Vazquez, Angel; Carmona-Galan, Ricardo (IEEE transactions on instrumentation and measurement, 2022)
FPGA-based time-to-digital converters (TDCs) are required to be accurate, linear, and fast, while at the same time employing a reduced number of resources. Pushing these requirements to the limit is challenging, although it is constantly required by many applications. This article presents a dual-mode tapped-delay-line (TDL)-propagating 1's and 0's in alternating measurement cycles-architecture for a field-programmable gate array (FPGA)-based TDC that complies with the mentioned specifications. The dead-time of the proposed TDC is reduced to one system clock cycle by using a toggling input stage and a dual-mode counter-based encoder. To improve the TDC linearity, the TDL sampling sequence is tuned separately for each operating mode. The presented architecture employs a low-resources dual-mode combinatory encoder of one- and zero-counters to remove the bubbles and cover both operating modes. A dual-mode bin-width calibration has been carried out to improve the TDC performance in each mode. The proposed architecture has been implemented on a Xilinx Artix-7 FPGA. Experimental results have shown a differential nonlinearity (DNL) within [−0.71 1.05] least significant bit (LSB) and an integral nonlinearity (INL) within [−0.85 0.86] LSB for the propagation of 1's. DNL and INL are within [−0.73 1.06] LSB and [−1.17 0.04] LSB, respectively, for the propagation of 0's. The LSB size is 22.1 ps and the TDC precision is 22.35 ps. A comparison with recently published state-of-the-art FPGA-based TDCs is provided at the end of the article.